Immunosuppressive medication is not associated with surgical site infection after surgery for intractable ulcerative colitis in children - Uchida, Keiichi (Intractable Rare Dis Res, 2017)
Pediatric ulcerative colitis (UC) sometimes progresses to an intractable condition for medical therapy. The surgical management of UC is challenging because of difficult procedures and frequent infectious complications. The aim of this study was to survey surgical procedures and infectious complications in pediatric patients with UC in Japan and to assess the relationship between preoperatively administered immunosuppressive drugs and postoperative surgical site infection (SSI). A survey of pediatric patients treated from 2000 to 2012 was sent to 683 facilities nationwide. Secondary questionnaires were sent to physicians who followed up patients with UC who had undergone surgery with the aim of assessing the relationships between postoperative SSI and selected preoperative patient characteristics, disease severity, medications, and operative procedures. Data for 136 patients (77 boys and 59 girls) were assessed. Median age at surgery was 14.1 years (range: 2.4–18.9 years). Surgery was performed in one stage in 35 cases, two stages in 57 cases, and three stages in 44 cases. SSI occurred in 36/136 patients (26%). According to multiple logistic regression analysis, there were statistically significant associations between SSI and staged surgery (three/one, OR: 6.7, 95% CI: 2.1–25.5, p = 0.0007; three/two, OR: 3.4, 95% CI: 1.4–8.6, p = 0.0069) and female sex (OR: 2.3, 95% CI: 1.0–5.4, p = 0.0434). Preoperative medications and incidence of SSI were not significantly associated. Preoperative immunosuppressive medication does not affect the incidence of SSI. Three-stage surgery and female sex are independent predictors of development of postoperative SSIs in pediatric patients with UC.